Specimen oriented intraoperative margin assessment in oral cavity and oropharyngeal squamous cell carcinoma - P. Horwich; C. MacKay; M. Bullock; S. M. Taylor; R. Hart; J. Trites; L. Geldenhuys; B. Williams; M. H. Rigby (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective Evaluate the oncologic outcomes and cost analysis of transitioning to a specimen oriented intraoperative margin assessment protocol from a tumour bed sampling protocol in oral cavity (OCSCC) and oropharyngeal squamous cell carcinoma (OPSCC). Study design Retrospective case series and subsequent prospective cohort study Setting Tertiary care academic teaching hospital Subjects and methods Retrospective case series of all institutional T1-T2 OCSCC or OPSCC treated with primary surgery between January 1st 2009 – December 31st 2014. Kaplan-Meier survival estimates with log rank tests were used to compare patients based on final margin status. Cost analysis was performed for escalation of therapy due to positive final margins. Following introduction of a specimen derived margin protocol, successive prospective cohort study of T1-T4 OCSCC or OPSCC treated with primary surgery from January 1st 2017 – December 31st 2018. Analysis and comparison of both protocols included review of intraoperative margins, final pathology and treatment cost. Results Analysis of our intra-operative tumour bed frozen section protocol revealed 15 of 116 (12.9%) patients had positive final pathology margins, resulting in post-operative escalation of therapy for 14/15 patients in the form of re-resection (7/14), radiation therapy (6/14) and chemoradiotherapy (1/14). One other patient with positive final margins received escalated therapy for additional negative prognostic factors. Recurrence free survival at 3 years was 88.4 and 50.7% for negative and positive final margins respectively (p = 0.048). Implementation of a specimen oriented frozen section protocol resulted in 1 of 111 patients (0.9%) having positive final pathology margins, a statistically significant decrease (p < 0.001). Utilizing our specimen oriented protocol, there was an absolute risk reduction for having a final positive margin of 12.0% and relative risk reduction of 93.0%. Estimated cost avoidance applying the specimen oriented protocol to our previous cohort was $412,052.812017 CAD. Conclusion Implementation of a specimen oriented intraoperative margin protocol provides a statistically significant decrease in final positive margins. This change in protocol leads to decreased patient morbidity by avoiding therapy escalation attributable only to positive margins, and avoids the economic costs of these treatments. Graphical abstract